Pengaruh penambahan arang aktif dengan metode steam blanching terhadap kadar kalsium oksalat dan glukomanan tepung umbi porang (Amorphophallus oncophyllus) - Malse Anggia; Ariyetti Ariyetti (AGROINTEK, 2023)
Porang is one of the plants having high glucomannan content. Porang which glucomannan will experience problems if the porang are processed into food ingredients with the presence of oxalate compounds in the porang. This study aims to determine the effect of adding activated carbon in steamed porang tubers to decrease calcium oxalate and determine the most appropriate concentration that should be added to porang tubers to produce porang tuber flour with optimum glucomannan content. The method used was a completely randomized design (CRD) with 5 treatments (addition of activated carbon 0 %, 2 %, 4 %, 6 %, and 8 %) and 3 replications. The results showed that the yield, water content, and glucomannan content of the resulting porang flour had no significant effect. In contrast, calcium oxalate levels significantly affected the addition of activated carbon. Optimum porang flour was found in addition 6 % activated carbon with 14,79 % yield, 0,16 % calcium oxalate, and 39,01 % glucomannan content. The moisture content of porang tuber flour is 8.84 % - 10.66 % already meets SNI Standard 7939:2013.